The political psychology of globalization Muslims in the West - Kinnvall, Catarina; Nesbitt-Larking, Paul W. (Oxford University Press, 2011)
In an increasingly globalized world, there are new economic, strategic, cultural, and political forces at work. The Political Psychology of Globalization: Muslims in the West explores how these shifts and shocks have influenced the way in which Muslim minorities in six western countries form their identities as political actors.